DEVELOPING LEARNING MATERIALS OBJECTORIENTED PROGRAMMING COURSE BLENDED BASED IN THE COVID-19 PANDEMIC PERIOD - Maspaeni; Suyitno Muslim; Nurdin Ibrahim (Journal of Islamic, Social, Economics and Development, 2022)
One of the competencies that computer students need to have in creating applicationsusing the concept of Object-Oriented Programming (OOP). The ability to make this applicationcan be measured based on student learning outcomes from OOP courses. By looking at thefinal scores of all computer students at the Faculty of Information and CommunicationTechnology (FICT) University of Technology Mataram (UTM) in the last three years, most ofthem scored below B, indicating that more than 50% of the students do not have the ability ornot so understand about making applications with the OOP concept. Based on a good analysisof student needs, problems were found. Through various studies, research was conducted todevelop learning materials to improve student learning outcomes of FICT UTM during thecovid-19 pandemic. This research was conducted using the Research and Development (R&D)method by combining the steps developed by Borg & Gall, Dick & Carey, Rowntree, and AllanJolliffe. Applying learning materials for OOP courses developed effectively could increasestudent learning outcomes by 50%. The effectiveness of this learning outcome was measuredbased on the results of testing the effectiveness of the product through the post-test with theresult that 85% of students were declared complete in achieving the expected minimumcompetency standard with an average score of 80.40 when compared to the score through thepre-test which averaged 57.20 with the number of students who were declared complete by35%.